A closer look: factors impacting HIV durable viral suppression among a cohort of clinic attendees in Trinidad & Tobago - Elena Cyrus; Deidre A. Okeke; Omari Lavia; Mary Jo Trepka; Allysha Maragh-Bass; Lunthita Duthely; Michael Sciauodone; Jeffrey Edwards (HIV Research & Clinical Practice)
Background In Trinidad and Tobago, high HIV prevalence among key populations necessitates studying factors that impact durable viral suppression (DVS), crucial for effective HIV management and reducing transmission among at-risk networks. This study investigates these factors using clinical data from a major HIV care clinic in the Caribbean. Methods A retrospective analysis of 533 adult people with HIV (people) at MRFTT from 2017 to 2021 assessed the proportion achieving DVS, defined as a sustained viral load <200 copies/ml over one year. Initial univariate analysis characterized individuals with DVS, followed by bivariate analysis to explore socio-demographic differences. Significant variables from bivariate analysis were examined in a regression model to identify DVS covariates. Results The average age of the sample was 45 years (SD = 10.88), with 52.0% male and 72.1% of African descent. 31.5% achieved durable viral suppression (DVS). Those with DVS were predominantly women (54.1%), older (mean age 45, SD = 11.32), with more frequent clinic visits over five years (mean = 101, SD = 33.26). Regression analysis showed that women (OR = 1.43, 95% CI 0.99–2.07), individuals on long-term antiretroviral therapy (ART) (>5 years) (OR = 1.66, 95% CI 1.03–2.66), and those with extended clinic enrolment (>5 years) (OR = 1.82, 95% CI 1.08–3.06) had higher odds of achieving DVS. Conclusions Only a third of the study sample achieved DVS, with men less likely to reach this goal. Lesser engagement in care correlated with lower DVS rates. Further research into social and structural barriers to clinic attendance, particularly among younger men, is recommended.